2013
DOI: 10.1016/j.mri.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A new perceptual difference model for diagnostically relevant quantitative image quality evaluation: A preliminary study

Abstract: Purpose Most objective image quality metrics average over a wide range of image degradations. However, human clinicians demonstrate bias toward different types of artifacts. Here, we aim to create a perceptual difference model based on Case-PDM that mimics the bias of human observers towards different artifacts. Method We measured artifact disturbance to observers and calibrated the novel PDM. To tune the new model, which we call Artifact-PDM, degradations were synthetically added to three healthy brain MR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…39 Sharma et al 23 (brain MRI), Worters et al 26 (spine MSI) and Zhang et al 29 (paediatric abdominal MRI) were the only studies we reviewed that systematically described artefacts observed in CS. In the study of brain MRI, artefacts became prominent and disruptive to diagnosis at acceleration factors .23.…”
Section: Compressed Sensing Artefactsmentioning
confidence: 99%
“…39 Sharma et al 23 (brain MRI), Worters et al 26 (spine MSI) and Zhang et al 29 (paediatric abdominal MRI) were the only studies we reviewed that systematically described artefacts observed in CS. In the study of brain MRI, artefacts became prominent and disruptive to diagnosis at acceleration factors .23.…”
Section: Compressed Sensing Artefactsmentioning
confidence: 99%
“…The rankings are then averaged and correlated with the similarity metrics. We should note that various quantitative measures, such as perceptual evaluation models, 34,35 have been used to evaluate MR image artifacts, such as blur, aliasing, and noise; but the focus here was on resolution, therefore we design the phantom study to compare images with a high-resolution scan. Expert evaluation is similarly performed to compare reconstructed images to the high-resolution reference scan.…”
Section: E Evaluation Methodsmentioning
confidence: 99%
“…They can be categorized into reference methods [12], [13], [14], [15], [16] and no-reference methods [17], [18], [19], [20], [21]. Detailed review of image quality evaluation for a general class of images and MRI images can be found in [22], [23], [24], [25], [26], [27], [28], [29].…”
Section: A Literature Reviewmentioning
confidence: 99%